In vitro Insecticidal and Time-Kill Profile of Ethyl Acetate Extract of Marine Streptomyces sp. Isolated from Sundarbans, Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
The marine soil and sediment samples were collected from different locations of mangrove forest Sundarbans, Bangladesh the largest tidal halophytic mangrove forest in the world. A total of twenty nine Actinomycete strains (AIAH-1 to AIAH-29) were isolated by serial dilution method using isolation media. Among twenty nine strains, AIAH-10 was selected for further study due to its potent antibacterial activity against a wide range of pathogenic bacterial strains. On the basis of morphological, cultural and biochemical studies, the strain AIAH-10 was assigned to Streptomyces sp. The present study was designed to investigate the in vitro insecticidal and time-kill profile of ethyl acetate extracts of marine Streptomyces sp. A dose dependent mortality was observed against the larvae of Sitophilus oryzae. The larval mortality was recorded as 100% in the concentration of 80 mg/ml and higher concentrations, LC50 was found as 11.48 mg/ml. The minimum inhibitory concentration was recorded as 8 to 32 mg/ml against six different pathogenic bacterial strains. Average Log10 reductions in viable cell counts for the extracts ranged from 1.91 Log10 and 2.86 Log10 cfu/mL after 3 h interaction and 2.10 Log10 and 2.93 Log10 after 6 h interaction at MIC, 2 × MIC, 3 × MIC and 4 × MIC concentrations. This investigation reveals that the Streptomyces species isolated from Sundarbans, Bangladesh may be interesting source for the isolation of potent bioactive compounds. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22332 Bangladesh Pharmaceutical Journal 17(2): 151-156, 2014